Impact of gene mutations and chromosomal aberrations on progression-free survival in chronic lymphocytic leukemia patients treated with front-line chemoimmunotherapy: Clinical practice experience. (June 2019) - Spunarova, Michaela; Tom, Nikola; Pavlova, Sarka; Mraz, Marek; Brychtova, Yvona; Doubek, Michael; Panovska, Anna; Skuhrova Francova, Hana; Brzobohata, Anna; Pospisilova, Sarka; Mayer, Jiri; Trbusek, Martin
Highlights: Unmutated IGHV status associates with reduced PFS in CLL patients treated with FCR. Deletion 11q22 associates with reduced PFS in CLL patients treated with FCR and BR. Sole deletion 11q22 without ATM mutation associates with the shortest PFS at all. Abstract: The impact of genetic aberrations on rituximab-based therapeutic regimens has been intensely studied in chronic lymphocytic leukemia (CLL). According to the current consensus chemoimmunotherapy consisting of rituximab and DNA-damaging drugs is not suitable for patients with TP53 defects. In our study, we focused on CLL patients with an intact TP53 gene and investigated four recurrently mutated genes in CLL, genomic aberrations by FISH, and IGHV status with the aim of analyzing their impact on progression-free survival (PFS) after front-line therapy with FCR (fludarabine, cyclophosphamide, rituximab) or BR (bendamustine, rituximab) regimens. Using next-generation sequencing, we analyzed 120 patients treated with FCR and 57 patients treated with BR at a university hospital. We used a 10% cut-off for variant allele frequency and recorded the following mutation frequencies in the pre-therapy samples: ATM 23%, SF3B1 20%, NOTCH1 19% and BIRC3 11%. The data on cytogenetic aberrations (11q22, 13q14, trisomy 12) and IGHV mutation status were also considered in PFS analyses. In univariate analyses, we observed a negative impact of BIRC3 mutations and 11q22 deletion in both regimens, while the unmutated IGHV status was associated with a significantly shorter PFS only in the FCR-treated cohort. In a multivariate analysis, only deletion 11q22 in both regimens, and the unmutated IGHV in the FCR cohort maintained an independent association with the reduced PFS. Notably, sole 11q22 deletion, without an ATM mutation on the other allele, manifested the shortest PFS of all analyzed markers. Deletion 11q22 and IGHV status predict PFS in previously untreated CLL patients.